The mastermind plot - Frazier, Angie (Scholastic Press, 2012)
In 1904, eleven-year-old Suzanna is delighted with her grandmother's invitation to spend time in Boston and thrilled to help her famous uncle investigate a series of arsons, but much less pleased to be enrolled her in Miss Lydia Doucette's Academy for Young Ladies.